Efforts of Counseling Guidance Teachers in Increasing the Religiosity of Students - Nasution, Rahmad Fauzi; Wijaya, Candra; Syarqawi, Ahmad (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
This study aims: 1) To describe efforts to increase the religiosity of students carried out by guidance counseling teachers at MAS Al Asy'ari Medan Krio, 2) To find out the supporting and inhibiting factors that the guidance and counseling teachers go through in an effort to foster the religiosity of students at MAS Al Asy'ari Medan Krio. The research method used in this study is a qualitative method. Data collection carried out in this study includes: 1) Observation, 2) Interview and 3) Documentation. The results of this study are that: 1) Guidance and counseling teachers' efforts to improve the religiosity of students are by providing assistance and advice so that they can overcome all student problems that occur in madrasas. 2) The supporting factors for guidance and counseling teachers in increasing the religiosity of students are internal and external factors. 3) The inhibiting factors for guidance and counseling teachers in increasing the religiosity of students are internal and external factors.